Analysis Of Calculation Of Cost Of Cost Of Production (Hpp) In The Dusun Coffee Business In Talang Benuang Air Periukan District, Seluma District - Willy Agustina; Ida Anggriani; Wagini Wagini (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
The aim of the research is to analyze the calculation of the cost of production (HPP) at the Dusun Coffee Business in Talang Benuang, Air Periukan District, Seluma Regency. The analytical method used in this research is the comparative descriptive method. Based on the calculation of the cost of production carried out by Dusun Coffee Business in Talang Benuang, Air Periukan District, Seluma Regency, the cost of production of ground coffee per pack of 250 gr is IDR. 15.263.-. and determining the selling price based on the market price, namely IDR. 25,000 so that the profit obtained is Rp. 9,737 per pack. Based on the full costing method, the basic production price for ground coffee per bag is Rp. 20,133,-. By setting the selling price at 25% of the cost of production, the total selling price of ground coffee per pack is IDR. 25,000,- so that the profit obtained is Rp. 4,876 per pack. There is a difference in the calculation of the cost of production between the company's calculation and the full costing method. The company method only calculates the costs of raw materials and auxiliary materials, while the full costing method performs more detailed calculations by calculating all cost components, namely raw material costs, labor costs, factory overhead costs and non-production costs.